Peningkatan Kualitas Penanganan Buah Kurma di UMK Sehat Alami Jogja melalui Pelatihan Quality Control - Syamsul Ma'arif; Elly Wuryaningtyas Yunitasari; Alvito Shultan Alfiansyah (Seminar Nasional Penelitian dan Abdimas, 2023)
Quality control is an essential aspect in maintaining product quality, including in the handling of dates fruit. UMK Sehat Alami Jogja faces challenges in implementing effective quality control practices. Therefore, the objective of this community engagement is to enhance the understanding of quality control practices in the handling of dates fruit at UMK Sehat Alami Jogja. The training was conducted online via the Zoom application. Through this training, significant results were obtained, as evidenced by the increased level of understanding in quality control for dates fruit and the comprehension of quality control practices in its handling. Respondents demonstrated improved overall understanding of quality control, particularly in relation to dates fruit and its handling methods. The findings of this activity conclude that online training is effective in enhancing quality control practices in the handling of dates fruit at UMK Sehat Alami Jogja. Additionally, recommendations are provided for future activities to enhance interaction and interactive discussions during the training, as well as to include more specific case studies related to the handling of dates fruit.